2021
DOI: 10.1016/j.lanwpc.2021.100223
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for being unsure or unwilling regarding intention to take COVID-19 vaccine among Japanese people: A large cross-sectional national survey

Abstract: Background Identifying and understanding reasons for being unsure or unwilling regarding intention to be vaccinated against coronavirus disease (COVID-19) may help to inform future public health messages aimed at increasing vaccination coverage. We analyzed a broad array of individual's psychological dispositions with regard to decision-making about COVID-19 vaccination in Japan. Methods A nationally representative cross-sectional web survey was conducted with 30053 Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
143
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(175 citation statements)
references
References 60 publications
25
143
1
6
Order By: Relevance
“…Besides, Shuhei Nomura and colleagues reported an overall 56.1% of respondents answering "yes" regarding their intention to have COVID-19 vaccination, which was said to be comparable to the results in similar surveys in western countries [1] . However, such intention, seemingly, has not been effectively translated into actual vaccination coverage which still fell short of 40% in Japan in July 2021 [4] .…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Besides, Shuhei Nomura and colleagues reported an overall 56.1% of respondents answering "yes" regarding their intention to have COVID-19 vaccination, which was said to be comparable to the results in similar surveys in western countries [1] . However, such intention, seemingly, has not been effectively translated into actual vaccination coverage which still fell short of 40% in Japan in July 2021 [4] .…”
supporting
confidence: 57%
“…In The Lancet Regional Health -Western Pacific , Shuhei Nomura and colleagues reported their interesting findings of a large-scale survey in Japan on COVID-19 vaccination intentions [1] . It is one of the largest surveys studying factors associated with the vaccination intention [2 , 3] .…”
mentioning
confidence: 99%
“…The rate of vaccination hesitancy is higher among cancer patients than among the general population. For example, a Chinese cross-sectional survey reported that only 8.7% of healthy adults were unwilling to receive the vaccine [31] ; in Australia, 6% of the population refused the vaccine [32] , and in Japan, 11.0% of respondents refused to take the COVID-19 vaccine [33] . Lack of faith in the efficacy and safety of vaccines is often cited as a main factor in vaccine hesitancy in various countries [34] , [35] , [36] , [37] , [38] .…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 , 29 , 30 In this study, the set of ( L j , β j ) was first estimated using the simulated annealing algorithm, and then we estimated (α 0 , α j ) after plugging the estimated ( L j , β j ) into the model using the maximum likelihood method. Based on previous studies, 16 , 25 , 26 , 31 , 32 the vector Z j includes the following socio-demographic and health-related covariates (see Table 1 for more detailed sub-categories): Occupation type (categorical), 16 , 25 , 31 Income (continuous) 27 , 31 , 32 Education level (continuous), 25 , 31 , 32 Gender (category of women, men or others), 26 , 31 and underlying diseases (categorical). 26 We asked the existence of underlying diseases such as “do you have an underlying disease (diabetes, heart failure, and respiratory disorders [COPD], etc.)?…”
Section: Methodsmentioning
confidence: 99%